Four weeks of intensified training enhances on-ice intermittent exercise performance and increases maximal oxygen consumption of youth national-team ice hockey players - Jeppesen, J. S.; Vigh-Larsen, J. F.; Oxfeldt, M. S.; Laustsen, N. M.; Mohr, M.; Bangbo, j.; Hostrup, M. (International Journal of Sports Physiology and Performance, 2022)
Purpose: We investigated whether 4 weeks of intensified training consisting of speed endurance training (SET) enhanced high-intensity exercise performance in youth national-team ice hockey players.